Pelatihan Pembuatan Lilin Aromaterapi dari Minyak Jelantah sebagai Inovasi Ekonomi Kreatif Generasi Muda Dusun Lilin - Suardana, Ida Bagus Putu; Suardana, I Ketut Putu; Laksmi, Ida Ayu Nyoman Widya; Yasa, I Komang Widya Purnama (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2025)
The development of the creative economy through training on converting used cooking oil waste into aromatherapy candles was conducted in Dusun Lilin, Giri Tembesi Village, from June 25 to August 9, 2025. This community service program was designed to enhance the ability of youth aged 12-22 to manage waste into economically valuable products through a training-based approach. The methods applied included observation, lectures, and hands-on practice involving 22 participants. The training program consisted of four main stages: 1) introduction to the program and the concept of the creative economy; 2) delivery of material regarding used cooking oil waste; 3) training in aromatherapy candle production; and 4) techniques for product packaging and marketing. Evaluation was conducted through direct observation of participants’ practical skills and interactive discussions to assess their understanding of the material and entrepreneurial interest. The results indicated that 85% of participants were able to understand the candle production process, 80% mastered basic packaging concepts, and 70% expressed interest in developing their own business. The products produced were four lavender-scented aromatherapy candles with a burning time of 4-6 hours and a long-lasting fragrance. From an economic analysis perspective, the potential profit reached IDR 45,000 from an investment of IDR 35,000 for four candles. The program proved effective in raising environmental awareness, fostering entrepreneurial spirit, and strengthening the creative economic skills of rural youth, while also offering an alternative solution for sustainable waste management.